Flame-retardant polycarbonate composite material and preparation method thereof
By using organic boron-based flame retardant prepared by triazine aniline derivative and formylphenylboronic acid acetate derivative, combined with polycarbonate and other flame retardants, a flame retardant polycarbonate composite material with stable light transmission performance under high temperature environment was prepared, which solved the problem of degradation of light transmission performance of existing materials and achieved a good balance between flame retardant and transmission performance.
Patent Information
- Application Number
- CN202411846473.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
After the existing polycarbonate composite materials are used in long-term high-temperature environments, their light transmittance performance will decline, affecting the aesthetics and the expansion of application fields.
A organic boron-based flame retardant was prepared by reacting triazine aniline derivative and formylphenylboronic acid acetate derivative, and mixed with polycarbonate, phosphate flame retardant and antioxidant. The flame retardant polycarbonate composite material was prepared through a twin screw extrusion mechanism.
The flame retardant performance of composite materials is significantly improved, and the high light transmittance is retained after high temperature aging, achieving a good balance between flame retardant and transmission performance.
Smart Images

Figure BDA0005189335620000021 
Figure BDA0005189335620000023 
Figure BDA0005189335620000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant polycarbonate, and particularly relates to a flame retardant polycarbonate composite material and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) is a high molecular polymer containing carbonate groups in the molecular chain. It is known for its outstanding optical properties and high impact strength. It also has good dimensional stability and electrical insulation properties. It is widely used in the fields of automobiles, medical treatment, construction, food packaging, aerospace, electronic appliances, lighting systems, etc. Due to the aromatic structure in the PC macromolecular chain, its flame retardant properties are better than PE and PP. The limiting oxygen index (LOI) can reach 21-24%, and the UL-94 flame retardant grade is V-2. However, PC often needs to meet more stringent flame retardant requirements in actual applications.
[0003] Boron flame retardants have the characteristics of high thermal stability, low toxicity, and smoke suppression, which are in line with the development trend of flame retardants being halogen-free, non-toxic or low-toxic, and smoke-suppressing. Boron flame retardants include inorganic boron flame retardants and organic boron flame retardants. Inorganic boron flame retardants have been studied relatively early, and common ones include ammonium pentaborate, sodium metaborate, ammonium fluoroborate, barium metaborate, and zinc borate, such as the flame-retardant light-stable polycarbonate and its preparation method disclosed in CN106280377B, and the composite flame retardant includes expandable graphite, nano carbonyl iron powder, zinc borate, graphene, and silane coupling agent; however, the amount of inorganic boron flame retardant added is relatively large, and it has a significant deterioration effect on the mechanical properties of PC. The research on organic boron flame retardants is relatively late. For example, CN112980173B discloses an antibacterial polycarbonate plastic, in which the organic flame retardant is melamine phosphate borate. Compared with inorganic boron flame retardants, it has less effect on the mechanical properties of PC, and can effectively improve the flame retardant properties of polycarbonate, and improve its mechanical properties to a certain extent. However, the study found that after the composite material has been working in a high temperature environment for a long time, plaques will appear on the surface and the light transmittance will decrease. This phenomenon not only affects the aesthetics of the material, but also seriously limits its application in fields that need to work in a high temperature environment for a long time and have strict requirements on light transmittance. It is speculated that the compatibility of organic boron flame retardants with polycarbonate is general. Although it has little effect on the mechanical properties and optical properties of the composite material at room temperature, if it works in a high temperature environment for a long time, the molecular motion of the organic boron flame retardant will be aggravated, resulting in an increase in its degree of freedom in the flame-retardant polycarbonate composite material, thereby migrating, gradually gathering to the surface, and decreasing light transmittance.
[0004] Therefore, developing an organic boron flame retardant with excellent compatibility with polycarbonate, good flame retardant properties and long-term high-temperature stable optical properties is of great significance for expanding and enhancing the application of polycarbonate in long-term high-temperature environments. Summary of the invention
[0005] In order to solve the problem of decreased transmittance after long-term high-temperature operation due to the above-mentioned compatibility, the present invention provides a flame-retardant polycarbonate composite material and a preparation method thereof, wherein an organic boron flame retardant is prepared by reacting a triazine aniline derivative and a formylphenylboronic acid acetate derivative. The organic boron flame retardant not only significantly improves the flame retardant properties of the composite material, but also has a higher light transmittance retention value after high-temperature aging, thereby achieving a good balance between flame retardancy and transmittance properties.
[0006] In order to achieve the above purpose, the following technical solutions are adopted:
[0007] A flame retardant polycarbonate composite material comprises the following raw materials in parts by weight: 100 parts of polycarbonate, 3-5 parts of an organic boron flame retardant, 2-3 parts of a phosphate flame retardant, and 0.1-0.5 parts of an antioxidant, wherein the organic boron flame retardant has a structural formula as shown in the following formula I: Formula I:
[0008]
[0009] Among them, R is selected from One or a combination of the two.
[0010] The organic boron flame retardant structural formula is selected from one or a combination of two or more of the following formulas Ⅰ-1, Ⅰ-2, Ⅰ-3, Ⅰ-4,
[0011]
[0012]
[0013] The organic boron flame retardant is prepared by reacting a triazine aniline derivative and a formylphenylboronic acid acetate derivative, wherein the molar ratio of the triazine aniline derivative to the formylphenylboronic acid acetate derivative is 1:3.15-3.3.
[0014] The triazine aniline derivative is selected from one or a combination of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 4',4"',4""'-(1,3,5-triazine ring-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)); the formylphenyl boric acid acetate derivative is selected from one or a combination of 4-formylphenyl boric acid methyliminodiacetate, 3-formylphenyl boric acid methyliminodiacetate.
[0015] Specifically, the organic boron flame retardant is prepared by a method comprising the following steps:
[0016] Under an inert atmosphere, an organic solvent, a triazine aniline derivative, and a formylphenylboronic acid acetate derivative are added to a reaction kettle and stirred until completely dissolved, and the temperature is raised to a reflux state for reaction. After the reaction is completed, the reaction is cooled to room temperature, and an organic alcohol is poured until no precipitation is generated. The organic boron flame retardant is filtered, washed, and dried.
[0017] The organic solvent is selected from one or a combination of two or more of benzene and toluene. The reaction time is 1-3 hours. The organic alcohol is selected from one or a combination of two or more of methanol, ethanol and isopropanol. The washing is 1-3 times of washing with organic alcohol. The drying is drying at 60-100° C. to constant weight.
[0018] The phosphate flame retardant is selected from one or a combination of two or more of triethyl phosphate, tributyl phosphate, triisooctyl phosphate, tri(2-butoxyethyl) phosphate, diphenyl isooctyl phosphate, diphenyl isodecyl phosphate, triphenyl phosphate, diphenyl cresyl phosphate, tricresyl phosphate, tricresyl phosphate, tricresyl phosphate, tricresyl phosphate, cumyl phosphate, and diphenyl (xylene) phosphate.
[0019] The polycarbonate is bisphenol A type polycarbonate with a melt index of 8-15 g / 10 min under the conditions of 300° C. and 1.2 kg.
[0020] The antioxidant is selected from one of antioxidant 1010, antioxidant 168, and antioxidant 164, or a combination of two or more thereof.
[0021] A method for preparing a flame retardant polycarbonate composite material comprises the following steps:
[0022] Polycarbonate, organic boron flame retardant, phosphate flame retardant and antioxidant are mixed evenly, and then added into a twin-screw extruder for extrusion, granulation and drying to obtain a flame-retardant polycarbonate composite material.
[0023] The twin-screw extruder has a screw speed of 20-100 r / min, a screw diameter of 10-40 mm, an aspect ratio of (12-40):1, and an extruder barrel temperature of 200-300°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention uses a triazine aniline derivative and a formylphenylboronic acid acetate derivative to react to prepare an organic boron flame retardant. The organic boron flame retardant not only significantly improves the flame retardancy of the composite material, but also has a higher light transmittance retention value after high-temperature aging, thereby achieving a good balance between flame retardancy and transmission performance.
[0026] The inventors found that triphenyl phosphate has a significant effect of synergizing with the organic boron flame retardant to reduce the heat release rate and increase the LOI value. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0028] Bisphenol A polycarbonate was purchased from Covestro with a grade of 2800 and a melt index of 10 g / 10 min.
[0029] Example 1
[0030] 1) Under nitrogen atmosphere, 200 mL of benzene, 0.1 mol of 4',4"',4""'-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)), and 0.315 mol of 4-formylphenylboronic acid methyliminodiacetate were added to a reaction kettle and stirred until completely dissolved, and the temperature was raised to reflux state to react for 3 h. After the reaction was completed, the mixture was cooled to room temperature, and isopropanol was poured until no new precipitation was generated. The residue was filtered, washed with ethanol for 3 times, and dried at 100° C. to obtain an organic boron flame retardant;
[0031] 2) 1000 g of polycarbonate Covestro 2800, 50 g of an organic boron flame retardant, 20 g of triphenyl phosphate, and 5 g of an antioxidant 1010 were mixed evenly, and then added to a twin-screw extruder for extrusion, granulation, and drying to obtain a flame-retardant polycarbonate composite material.
[0032] Among them, the screw speed of the twin-screw extruder is 70r / min, the screw diameter is 20mm, the aspect ratio is 20:1, and the extruder barrel temperature is 240℃, 260℃, 270℃, 265℃, and 260℃.
[0033] Example 2
[0034] The rest is the same as Example 1, except that in step 1), an equal molar amount of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is used to replace 4',4"',4""'-(1,3,5-triazinecyclo-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)).
[0035] Example 3
[0036] The rest is the same as Example 1, except that in step 1), 4-formylphenylboronic acid methyliminodiacetate is replaced by 3-formylphenylboronic acid methyliminodiacetate in an equal molar amount.
[0037] Example 4
[0038] The rest is the same as Example 1, except that in step 2), the amount of organic boron flame retardant used is 30 g.
[0039] Example 5
[0040] 1) Under nitrogen atmosphere, 200 mL of benzene, 0.1 mol of 4',4"',4""'-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)), and 0.33 mol of 4-formylphenylboronic acid methyliminodiacetate were added to a reaction kettle and stirred until completely dissolved, and the temperature was raised to reflux state to react for 3 h. After the reaction was completed, the mixture was cooled to room temperature, and isopropanol was poured into the reaction kettle until no precipitation was generated. The residue was filtered, washed with ethanol for 3 times, and dried at 100° C. to obtain an organic boron flame retardant;
[0041] 2) 1000 g of polycarbonate Covestro 2800, 30 g of an organic boron flame retardant, 30 g of triphenyl phosphate, and 5 g of an antioxidant 1010 were mixed evenly, and then added to a twin-screw extruder for extrusion, granulation, and drying to obtain a flame-retardant polycarbonate composite material.
[0042] Among them, the screw speed of the twin-screw extruder is 70r / min, the screw diameter is 20mm, the aspect ratio is 20:1, and the extruder barrel temperature is 250℃, 260℃, 270℃, 265℃, and 260℃.
[0043] Example 6
[0044] The rest is the same as Example 1, except that the amount of triphenyl phosphate used in step 2) is 30 g.
[0045] Comparative Example 1
[0046] The rest is the same as Example 1, except that in step 2), an equal mass of melamine phosphate borate is used to replace the organic boron flame retardant.
[0047] Wherein: melamine phosphate borate is prepared with reference to Zhao Aiming's "Synthesis of Melamine Phosphate Borate Flame Retardant" (Shandong Chemical Industry, Vol. 38, No. 12, 2009). The preparation method of melamine phosphate borate comprises the following steps: adding 17.02g 85wt% H3PO4 to 50mL water, stirring evenly and heating to 50°C, then adding 18.6g melamine and stirring evenly, reacting at 50°C for 2h, centrifuging to obtain a precipitate, washing and drying to obtain melamine phosphate; adding 6.70g boric acid and 16.2g melamine phosphate to 45mL water, stirring evenly, heating to 80°C for 3h, centrifuging to obtain a precipitate, washing and drying to obtain melamine phosphate borate.
[0048] Comparative Example 2
[0049] The rest is the same as Example 1, except that in step 2), triphenyl phosphate is not added.
[0050] Comparative Example 3
[0051] The rest is the same as Example 1, except that in step 2), the amount of organic boron flame retardant used is 25 g.
[0052] Comparative Example 4
[0053] The rest is the same as Example 1, except that the amount of triphenyl phosphate used in step 2) is 35 g.
[0054] The flame retardant polycarbonate composite materials prepared in the above examples and comparative examples were tested for the following properties:
[0055] Light transmittance: Tested according to ASTM D1003.
[0056] Heat aging: Refer to GB / T 7141-2008 Plastics Heat Aging Test Method, and re-test the transmittance after aging at 130℃ in an aging test chamber for 200 hours.
[0057] Flame retardant grade test: Test according to GB / T2408-2008 "Test of combustion performance of plastics - horizontal method and vertical method".
[0058] LOI: Tested in accordance with ASTM D2863.
[0059] Cone calorimetry test: Refer to ISO 5660-1, injection molded plate test, size 100mm×100mm×3.2mm, at 50kW / m 2 Peak heat release rate (PHRR) data were collected at a heat flux of 100 Å.
[0060] Table 1 Performance test results
[0061] project LOI UL-94 Transmittance after heat aging % Peak Heat Release Rate (PHRR) Example 1 36.4 V0 90 251 Example 2 30.5 V0 85 255 Example 3 36.3 V0 87 251 Example 4 28.7 V0 90 280 Example 5 32.8 V0 90 278 Example 6 33.9 V0 90 272 Comparative Example 1 32.6 V0 76 346 Comparative Example 2 26.2 V1 88 414 Comparative Example 3 21.7 V1 89 313 Comparative Example 4 38.1 V0 90 382
[0062] It can be seen from the transmittance test of heat aging that the organic boron flame retardant prepared by the present invention has good compatibility with the composite material and has little transmittance loss after high-temperature aging.
[0063] From Table 1, Example 1, Example 6, Comparative Example 2, and Comparative Example 4, it can be clearly seen that triphenyl phosphate has a significant effect of cooperating with the organic boron flame retardant to reduce the heat release rate and improve the LOI value. It is speculated that an appropriate amount of triphenyl phosphate can form a carbon layer with the organic boron flame retardant, reduce the transfer of combustible gases in the flame, and generate phosphorus-based and phosphorus-oxyl free radicals at the same time, play a free radical capture role, and thus effectively inhibit the heat release during the combustion process. However, when the amount of triphenyl phosphate is large, the heat release rate increases. It is speculated that the plasticization of excessive triphenyl phosphate causes the melt viscosity to decrease, which reduces the strength of the carbon layer, and thus has a higher heat release rate.
[0064] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A flame retardant polycarbonate composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polycarbonate, 3-5 parts of organic boron flame retardant, 2-3 parts of phosphate flame retardant, and 0.1-0.5 parts of antioxidant. The organic boron flame retardant has a structural formula as shown in the following formula I: Formula I: Among them, R is selected from One or a combination of the two.
2. The flame retardant polycarbonate composite material according to claim 1, characterized in that: The structural formula of the organic boron flame retardant is selected from one or a combination of two or more of the following formulas Ⅰ-1, Ⅰ-2, Ⅰ-3, Ⅰ-4, 3. The flame retardant polycarbonate composite material according to claim 1, characterized in that: The organic boron flame retardant is prepared by reacting a triazine aniline derivative and a formylphenylboronic acid acetate derivative, wherein the molar ratio of the triazine aniline derivative to the formylphenylboronic acid acetate derivative is 1:3.15-3.
3.
4. The flame retardant polycarbonate composite material according to claim 3, characterized in that: The triazine aniline derivative is selected from one or a combination of two of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 4',4"',4""'-(1,3,5-triazine ring-2,4,6-triyl)tris(([1,1'-biphenyl]-4-amine)).
5. The flame retardant polycarbonate composite material according to claim 3, characterized in that: The formylphenylboronic acid acetate derivative is selected from one or a combination of 4-formylphenylboronic acid methyliminodiacetate and 3-formylphenylboronic acid methyliminodiacetate.
6. The flame retardant polycarbonate composite material according to claim 1, characterized in that: The organic boron flame retardant is prepared by a method comprising the following steps: Under an inert atmosphere, an organic solvent, a triazine aniline derivative, and a formylphenylboronic acid acetate derivative are added to a reaction kettle and stirred until completely dissolved, and the temperature is raised to a reflux state for reaction. After the reaction is completed, the reaction is cooled to room temperature, and an organic alcohol is poured until no precipitation is generated. The organic boron flame retardant is filtered, washed, and dried.
7. The flame retardant polycarbonate composite material according to claim 6, characterized in that: The organic solvent is selected from benzene, toluene, or a combination of two or more thereof. The reaction time is 1-3 hours.
8. The flame retardant polycarbonate composite material according to claim 1, characterized in that: The phosphate flame retardant is selected from one or a combination of two or more of triethyl phosphate, tributyl phosphate, triisooctyl phosphate, tri(2-butoxyethyl) phosphate, diphenyl isooctyl phosphate, diphenyl isodecyl phosphate, triphenyl phosphate, diphenyl cresyl phosphate, tricresyl phosphate, tricresyl phosphate, tricresyl phosphate, tricresyl phosphate, cumyl phosphate, and diphenyl (xylene) phosphate.
9. The flame retardant polycarbonate composite material according to claim 1, characterized in that: The polycarbonate is bisphenol A type polycarbonate with a melt index of 8-15 g / 10 min under the conditions of 300° C. and 1.2 kg.
10. A method for preparing the flame retardant polycarbonate composite material according to any one of claims 1 to 9, characterized in that: The steps include: Polycarbonate, organic boron flame retardant, phosphate flame retardant and antioxidant are mixed evenly, and then added into a twin-screw extruder for extrusion, granulation and drying to obtain a flame-retardant polycarbonate composite material.
Citation Information
Patent Citations
Flame-retardant light-stabilized polycarbonate and its preparation method
CN106280377B
An antibacterial polycarbonate plastic
CN112980173B
High-flowability halogen-free flame-retardant polycarbonate, preparation method thereof and high-flowability halogen-free flame-retardant polycarbonate product
CN104231585A
Flame-retardant polycarbonate and preparation method thereof
CN109251503A
Flame-retardant resin composition
JP1993098144A
Cited By
Flame-retardant PVC composite material and preparation method thereof
CN121226925A
Flame-retardant PVC composite material and preparation method thereof
CN121226925B